HUBUNGAN TINGKAT PENDIDIKAN FORMAL DENGAN PARENTING SELF-EFFICACY PERIODE AWAL NIFAS PADA IBU PASCA SECTIO CAESAREA - Domas Chandra Pramudianti; Abkar Raden; Endang Koni Suryaningsih (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: The research aimsto determine the relationship of the level of formal education with parenting self-efficacy in the early period of postnatal maternal post Sectio Caesarea(SC).The methods is an observational study with cross sectional design. The study population includes all mothers post SC in RSIA 'Aisyiyah Klaten and Delanggu PKU Muhammadiyah Hospital, the subject of the study involved 66 people. Samples were selected purposively to the inclusion criteria of exclusion. Data analysis using Spearman Rank at the 95% confidence level. The results is level of formal education have a meaningful relationship with parenting self-efficacy in the early postnatal period with a value of p = 0.000 (p <0.05). Keywords: formal education, parenting self-efficacy